2019
DOI: 10.1016/j.ctro.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare ex Machina: Are conversational agents ready for prime time in oncology?

Abstract: Highlights Chatbots are artificial intelligence–driven programs that interact with people. They can be used for screening, treatment adherence and follow-up. They can be deployed as text-based services on a website or mobile applications. Potential applications are very promising in our field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 21 publications
0
49
0
2
Order By: Relevance
“…Studies have shown that PDI has a good internal consistency, stability, and validity. PDI items can be grouped into factors that better reflect and predict PD and PTSD: negative emotions (items 1, 2, 3, 5, 6, 8, and 10) and perceived life threat and bodily arousal (items 4,7,9,11,12, and 13) (9). It has also been shown that a PDI score equal or over 14 was predicting full or partial PTSD six-weeks post-injury (10).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that PDI has a good internal consistency, stability, and validity. PDI items can be grouped into factors that better reflect and predict PD and PTSD: negative emotions (items 1, 2, 3, 5, 6, 8, and 10) and perceived life threat and bodily arousal (items 4,7,9,11,12, and 13) (9). It has also been shown that a PDI score equal or over 14 was predicting full or partial PTSD six-weeks post-injury (10).…”
Section: Introductionmentioning
confidence: 99%
“…But, the authors noted that the few published studies were mainly quasi-experimental, and rarely evaluated efficacy or safety. Bibault et al [9] made the same observation, if chatbots are shown to be effective and safe, they could be prescribed like any drug to improve patient information, monitoring, or treatment adherence. Chaix et al [2] showed that a chatbot designed to help patient with breast cancer could improve medication adherence.…”
Section: Introductionmentioning
confidence: 93%
“… 16 That said, a recent review reported that most healthcare applications of chat bots lack sufficient validation of clinical outcomes. 25 This is a crucial step that is needed for these solutions to be safely deployed. 26 Therefore, while these solutions may be useful to scale up patient support for mental health and self-management, any deployed solutions should be closely monitored for performance.…”
Section: Conversational Artificial Intelligencementioning
confidence: 99%